STATUS KEBERLANJUTAN DAN STRATEGI PENGEMBANGAN KAWASAN MINAPOLITAN PERIKANAN BUDIDAYA DI KABUPATEN SERAM BAGIAN BARAT - Karepesina, Musa; Abrahamsz, James; Lopulalan, Yoisye (Program Studi Agrobisnis Perikanan, Universitas Pattimura, 2019)
This study aims to determine the existing conditions, analyze the level of sustainability and formulate priority policies for the development of the minapolitan Region in West Seram Regency. The analytical method used in this study includes descriptive analysis, Rapfish analysis, and Analitycal Hierarchy Process (AHP). An assessment of the existing conditions shows that the geographical location is a potensial area, has superior commodities, and production units, limited of facilities and processing infrastructure, and the lack of market information and marketing institutions to  support the business process and needs to be improved in order to develop the minabisnis in minapolitan area. The analytical results of the  sustainable status in the ecological, economic and institutional dimensions obtain an index value that is quite sustainable, and the social dimension in technology receives a index value in a sustainable manner. Institutional factor is a criterion that becomes the main priority in the direction of the development of the minapolitan area in Kotania Bay. So that it is necessary to increase the role of local government to optimally utilize the potential of aquaculture.